A Comprehensive Financial and Organizational Analysis of Telerehabilitation Business Models for Sustainable Growth and Market Expansion in the Healthcare Sector - Dhirenbhai Kalal (The Eastasouth Management and Business, 2024)
This shift marked the end of the pandemic era, where telerehabilitation was merely an emergency measure, and the beginning of a new growth trajectory for digital health, with the global market estimated at USD 5.32 billion in 2024 and projected to grow to USD 11.81 billion by 2030 at a CAGR of 13.2 per cent. However, the financial and organisational basis of this growth is poorly documented, to varying degrees, in the different clinical indications. This paper presents a financial and organisational evaluation of fourteen peer-reviewed and industry-based sources to create a holistic view of business models for telerehabilitation. Evidence is presented under three themes: Business model frameworks in digital health, Health-economic evidence for telerehabilitation, and Clinical and organisational implementation. Results found that per-patient savings ranged from USD 565.66 to USD 2,352.00, with four of eight studies showing moderate results for combined neurological and cardiological populations; per-patient savings were found to be favourable, with ninety-two per cent of reviewed cardiac studies showing favourable results for protocolized, exercise-based cardiac interventions; and results were least consistent for heterogeneous musculoskeletal indications. Financial sustainability of telerehabilitation businesses was identified through business model syntheses as having common elements such as diversified revenue streams, partnerships with payers and with technology vendors, and adaptive governance. Analysis shows that rather than a common telerehabilitation approach, business model design is the most defendable path to sustainable market expansion.